The Practice of Indonesia’s Environmental Reporters: Competence and Challenges - Gilang Desti Parahita (AJMC (Asian Journal of Media and Communication), 2017)
Indonesia’s environmental reporting has been dynamically developed as it has been influenced by the interlinked factors of freedom of the press, media conglomeration, and the emergence of online technology. Regarding to those factors, how are the competence of the Indonesia’s environmental reporters? How do Indonesia’s environmental reporters perceive challenges? This research conducts survey and interviews to Indonesia’s environmental reporters who are also the members of the Society of Indonesia’s Environmental Journalist (SIEJ).Keywords: Journalism practices, environmental journalism